Historyography of the Investigation of Foreign Languages Teaching Problem in the Contest of Real Native Education Tendencies Development (late XIX early XX century) - Honcharenko, Natalia (Pedagogical Discourse, 2013)
Historyographical review of the sources has been made and the state of the investigation offoreign languages teachingproblem in the contest of real native education tendencies developmentof late XIX early XX century has been defined. It was defined that scientists in their researchers paid attention to such problems of the investigation as: secondary school development, reformation of educational system, statement and functioning of real secondary schools, advantages of classical and real education, methodology of some subjects teaching in real secondary schools, the educational processimprovement, enlighten of pedagogs’views on the primary and secondary education, analysis of the discussions aroud classicism and realism and projects of the gymnasium regulations, the process of introducing and spreading of foreign languages in different types of secondary educational establishments, history of the forming of organizing principles, content and form of of foreign languagesteachers’ training.